ANALYSIS ENHANCE OF SERVICE PEOPLES CONCERNING MENTAL HEALTH - Hutri Ayu Dwisartika; Redyanto Sidi; Beni Satria (SEAN Institute, 2023)
This study aims to analyze the legal protection of Persons with Mental Disorders (ODGJ) in the context of health services based on Indonesian Law No. 18/2014 on Mental Health. Legal protection is a human right that must be provided to every individual, including ODGJ, who require equal access to quality mental health services. This research uses the normative legal research method by examining legislation, doctrine, and legal principles relevant to the legal protection of ODGJ. In order to improve the legal protection of ODGJ, this study recommends several strategic steps, such as improving legislation, improving the quality and affordability of mental health services, and education and advocacy campaigns to reduce stigma and discrimination against ODGJ.